One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Notch1-MAPK signaling axis regulates CD133+ cancer stem cell-mediated melanoma growth and angiogenesis - Kumar, Dhiraj; Kumar, Santosh; Gorain, Mahadeo; Tomar, Deepti; Patil, Harshal S.; Radharani, Nalukurthi N. V.; Kumar, Totakura V. S.; Patil, Tushar V.; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (Journal of Investigative Dermatology, 2016)
Functional characterization and understanding of the intricate signaling mechanisms in stem-like cells is crucial for the development of effective therapies in melanoma. We have studied whether melanoma cells are phenotypically distinct and hierarchically organized according to their tumorigenic nature. We report that melanoma-specific CD133(+) cancer stem cells exhibit increased tumor-initiating potential, tumor-endothelial cell interaction, and lung metastasis. These cells are able to transdifferentiate into an endothelial-like phenotype when cultured under endothelial differentiation-promoting conditions. Mechanistically, Notch1 upregulates mitogen-activated protein kinase activation through CD133, which ultimately controls vascular endothelial growth factor and matrix metalloproteinase expression in CD133(+) stem cells leading to melanoma growth, angiogenesis, and lung metastasis. Blockade or genetic ablation of Notch1 and mitogen-activated protein kinase pathways abolishes melanoma cell migration and angiogenesis. Chromatin immunoprecipitation and reporter assays revealed that Notch1 intracellular domain regulates CD133 expression at the transcriptional level. Andrographolide inhibits Notch1 intracellular domain expression, Notch1 intracellular domaindependent CD133-mediated mitogen-activated protein kinase and activator protein-1 activation, and epithelial to mesenchymal-specific gene expression, ultimately attenuating melanoma growth and lung metastasis. Human malignant melanoma specimen analyses revealed a strong correlation between Notch1 intracellular domain, CD133, and p-p38 mitogen-activated protein kinase expression and malignant melanoma progression. Thus, targeting Notch1 and its regulated signaling network may have potential therapeutic implications for the management of cancer stem cell-mediated melanoma progression.

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K